the answer is D.31 because 21+10=31
hope i helped
Answer:
d just know it bc i did this
Step-by-step explanation:
The measure of the angle is 50°.
When the sum of two angles measures up to 180° then these angles are known as supplementary angles of each other.
for example, ∠x + ∠y = 180°, therefore, the ∠x and ∠y are the supplementary angles of each other.
When the sum of two angles measures up to 90° then these angles are known as complementary angles of each other.
for example, ∠x + ∠y = 90°, therefore, the ∠x and ∠y are the complementary angles of each other.
Let's assume that the angle is x.
The supplementary angle of x is (180°-x).
The complementary angle of x is (90°-x).
According to the question,
(180°-x) = 4(90°-x)-30°,
(180°-x) = 4(90°-x)-30°
180 - x = 360 - 4x - 30
4x - x = 360 - 30 -180
3x = 150
x = 50°
Hence, the measure of the angle is 50°.
Learn more about Supplementary and Complementary angles:
Answer:
(y+1)(2y−3)
Step-by-step explanation:
Answer:
3 1/2 =x
Step-by-step explanation:
(1/2) / 4 = x/28
Using cross products
1/2 * 28 = 4*x
14 = 4x
Divide each side by 4
14/4 = 4x/4
7/2 = x
3 1/2 =x
Answer:
Step-by-step explanation:
Cross Multiplying
=> 1/2 * 28 = 4x
=> 14 = 4x
=> 4x = 14
Dividing both sides by 4
=> x = 14/4
=> x = 7/2
=> x =
Thank u
Answer:
Step-by-step explanation:
Left
When a square = a linear, always expand the squared expression.
x^2 - 2x + 1 = 3x - 5 Subtract 3x from both sides
x^2 - 2x - 3x + 1 = -5
x^2 - 5x +1 = - 5 Add 5 to both sides
x^2 - 5x + 1 + 5 = -5 + 5
x^2 - 5x + 6 = 0
This factors
(x - 2)(x - 3)
So one solution is x = 2 and the other is x = 3
Second from the Left
i = sqrt(-1)
i^2 = - 1
i^4 = (i^2)(i^2)
i^4 = - 1 * -1
i^4 = 1
16(i^4) - 8(i^2) + 4
16(1) - 8(-1) + 4
16 + 8 + 4
28
Second from the Right
This one is rather long. I'll get you the equations, you can solve for a and b. Maybe not as long as I think.
12 = 8a + b
17 = 12a + b Subtract
-5 = - 4a
a = - 5/-4 = 1.25
12 = 8*1.25 + b
12 = 10 + b
b = 12 - 10
b = 2
Now they want a + b
a + b = 1.25 + 2 = 3.25
Right
One of the ways to do this is to take out the common factor. You could also expand the square and remove the brackets of (2x - 2). Both will give you the same answer. I think expansion might be easier for you to understand, but the common factor method is shorter.
(2x - 2)^2 = 4x^2 - 8x + 4
4x^2 - 8x + 4 - 2x + 2
4x^2 - 10x + 6 The problem is factoring since neither of the first two equations work.
(2x - 2)(2x - 3) This is correct.
So the answer is D